L1 USED DURING L2 FREE WRITING: A LOOK AT BEGINNING WRITERS - Nuraini, Indah (ELTICS Journal, 2015)
Abstract This research aims to investigate the composing process and writing strategiesofthe beginning writersâ free writing product dealing with the writing problem and theory of the writing process. It is seen from their grammar (minor grammatical errors, such as âs on verbs in third person singular), vocabulary (knows most words needed to express ideas but lacks vocabulary for finer shades of meaning), sentence (uses several sentences pattern), organization (somewhat sequenced), and fluency (writes several sentences). It focuses on how the beginning writersâ L1 influence their L2 free writing product. Twenty five (25) students invoked by producing twenty five (25) different topics. The result shows that there is an influence of L1 knowledge to L2 language production in which the participants translate their ideas in L1 knowledge to L2 language directly without considering the structures and forms. Keywords: free writing, beginning writer, writing process, scaffolding